Human Fc Receptor-like 3 Inhibits Regulatory T Cell Function and Binds Secretory IgA - Stuti Agarwal; Zachary Kraus; Jessica Dement-Brown; Oyeleye Alabi; Kyle Starost; Mate Tolnay (Cell Reports, 2020)
Summary: Human Fc receptor-like 3 (FCRL3) is an orphan receptor expressed by lymphocytes, including regulatory T cells. FCRL3 is implicated in several autoimmune diseases; however, its function on regulatory T cells is unknown. We discovered that FCRL3 stimulation of regulatory T cells inhibited their suppressive function. Moreover, FCRL3 stimulation induced IL-17, IL-26, and IFNγ production and promoted expression of the Th17-defining transcription factor RORγt without affecting FOXP3 expression. We suggest that FCRL3 engagement mediates a transition of regulatory T cells to a pro-inflammatory Th17-like phenotype. In addition, we identified secretory IgA as a specific FCRL3 ligand. Secretory IgA could serve as an environmental cue for mucosal breaches and locally drive regulatory T cell plasticity to help control infection. Our findings define a mechanism that explains the recognized association of FCRL3 with autoimmune diseases. Targeting FCRL3 to modulate regulatory T cell activity could be exploited to treat both malignancies and autoimmune diseases. : The key role of secretory IgA in neutralizing pathogens in mucosal surfaces is well established. Agarwal et al. propose that secretory IgA entering the body through breached mucosa engages FCRL3 on regulatory T cells and suppresses their inhibitory function. FCRL3 could be therapeutically targeted to modulate regulatory T cell activity. Keywords: regulatory T cell, secretory IgA, mucosal immunity, autoimmunity, inflammation, immunotherapy